2001
DOI: 10.1037/0882-7974.16.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of an old female eyewitness: Is the older eyewitness believable?

Abstract: Young adults rated an old female witness (82 years) to be less competent but more honest than a young female witness (28 years). The effect of age stereotyping on believability was assessed indirectly by using a variant of Loftus' misinformation paradigm. Regression analysis showed that the more competent a witness was perceived as being, the more influential was the misinformation she provided. This was true, however, only when the witness was young because the relatively lower competence of the old witness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 21 publications
4
60
2
4
Order By: Relevance
“…A literatura revela, também, que na sociedade em geral existem vários esquemas mentais sobre os idosos que incluem quer crenças positivas, quer negativas (Kwong See, Hoffman, & Wood, 2001). O aumento da idade dos adultos é muitas vezes percebido como associado a qualidades positivas, por exemplo, a honestidade, sinceridade (Ryan, Szechtman, & Bodkin, 1992) e negativas, como a fraca memória (Guo, Erber, & Szuchman, 1999).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A literatura revela, também, que na sociedade em geral existem vários esquemas mentais sobre os idosos que incluem quer crenças positivas, quer negativas (Kwong See, Hoffman, & Wood, 2001). O aumento da idade dos adultos é muitas vezes percebido como associado a qualidades positivas, por exemplo, a honestidade, sinceridade (Ryan, Szechtman, & Bodkin, 1992) e negativas, como a fraca memória (Guo, Erber, & Szuchman, 1999).…”
Section: Introductionunclassified
“…Até aos dias de hoje, a investigação sobre esta faixa etária no contexto forense, concentrou-se sobretudo, e quase exclusivamente, nas perceções dos juízes sobre as testemunhas idosas (Brimacombe, Jung, Garrioch, & Allison, 2003;Kwong See, Hoffman, & Wood, 2001). Contudo, é igualmente importante considerar as atitudes dos órgãos de polícia criminal, já que são eles a primeira autoridade a estar em contacto com as testemunhas e a interrogá-las.…”
Section: Introductionunclassified
“…Relative to younger eyewitnesses, older adults are perceived as more honest, but less reliable (Kwong See, Hoffman, & Wood, 2001;Yarmey, 1984). Interestingly, research has also demonstrated that witness age has little impact on perceptions of guilt (Brimacombe et al, 1997), suggesting perhaps that these two trends offset each other in jurors' perceptions of witness credibility.…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…Interestingly, research has also demonstrated that witness age has little impact on perceptions of guilt (Brimacombe et al, 1997), suggesting perhaps that these two trends offset each other in jurors' perceptions of witness credibility. A clever study by Kwong See et al (2001) examined the impact of stereotypic beliefs in a more indirect fashion by testing whether participants would modify their own memory reports based on inaccurate information about the same event provided by either a young or older witness. Consistent with research examining more explicit attitudes, these researchers found that stereotypes were operative in that younger adults were more likely to adjust their memory to be consistent with a young witness perceived to be high in competence than they were to an older witness of similar standing.…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…Kwong See, Hoffman, and Wood (2001) manipulated credibility of the source through varying the age of the co-witness. All participants were given a narrative of an event containing four pieces of misinformation and were told that it was received from either a 28 or 82 year old witness.…”
Section: Memory Conformitymentioning
confidence: 99%